APA ALASAN YANG MEMPENGARUHI WISATAWAN MENGUNJUNGI TUJUAN PARIWISATA? - Palupi, Shara Merry; Hadiyati, Ernani; Astuti, Rini (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to determine the effect of service quality and intention on visit decisions mediated by tourist satisfaction. Design/methodology/approach- Quantitative methods are used to explain the relationship between variables with SEM-PLS analysis techniques. Findings- The results showed the influence of service quality on intentions, service quality on tourist satisfaction, intentions on tourist satisfaction, tourist satisfaction on visit decisions, quality of service on visit decisions, and intention to make visit decisions. Implication/Limitation - The results of the study can be used as a reference in the formulation of new policies by local governments in tourism management, especially in Blitar, and other regions in general. This research has limitations on previous empirical evidence that explains the same phenomenon. Keywords: Service quality, intention, tourist satisfaction, visiting decision.